Intensive blood pressure control after endovascular thrombectomy for acute ischaemic stroke (ENCHANTED2/MT): a multicentre, open-label, blinded-endpoint, randomised controlled trial. Issue 10363 (5th November 2022) - Yang, Pengfei; Song, Lili; Zhang, Yongwei; Zhang, Xiaoxi; Chen, Xiaoying; Li, Yunke; Sun, Lingli; Wan, Yingfeng; Billot, Laurent; Li, Qiang; Ren, Xinwen; Shen, Hongjian; et al.
Summary: Background: The optimum systolic blood pressure after endovascular thrombectomy for acute ischaemic stroke is uncertain. We aimed to compare the safety and efficacy of blood pressure lowering treatment according to more intensive versus less intensive treatment targets in patients with elevated blood pressure after reperfusion with endovascular treatment. Methods: We conducted an open-label, blinded-endpoint, randomised controlled trial at 44 tertiary-level hospitals in China. Eligible patients (aged ≥18 years) had persistently elevated systolic blood pressure (≥140 mm Hg for >10 min) following successful reperfusion with endovascular thrombectomy for acute ischaemic stroke from any intracranial large-vessel occlusion. Patients were randomly assigned (1:1, by a central, web-based program with a minimisation algorithm) to more intensive treatment (systolic blood pressure target <120 mm Hg) or less intensive treatment (target 140–180 mm Hg) to be achieved within 1 h and sustained for 72 h. The primary efficacy outcome was functional recovery, assessed according to the distribution in scores on the modified Rankin scale (range 0 [no symptoms] to 6 [death]) at 90 days. Analyses were done according to the modified intention-to-treat principle. Efficacy analyses were performed with proportional odds logistic regression with adjustment for treatment allocation as a fixed effect, site as a random effect, and baseline prognostic factors, and included all randomly assigned patients who provided consent and had available data for the primary outcome. The safety analysis included all randomly assigned patients. The treatment effects were expressed as odds ratios (ORs). This trial is registered at ClinicalTrials.gov, NCT04140110, and the Chinese Clinical Trial Registry, 1900027785; recruitment has stopped at all participating centres. Findings: Between July 20, 2020, and March 7, 2022, 821 patients were randomly assigned. The trial was stopped after review of the outcome data on June 22, 2022, due to persistent efficacy and safety concerns. 407 participants were assigned to the more intensive treatment group and 409 to the less intensive treatment group, of whom 404 patients in the more intensive treatment group and 406 patients in the less intensive treatment group had primary outcome data available. The likelihood of poor functional outcome was greater in the more intensive treatment group than the less intensive treatment group (common OR 1·37 [95% CI 1·07–1·76]). Compared with the less intensive treatment group, the more intensive treatment group had more early neurological deterioration (common OR 1·53 [95% 1·18–1·97]) and major disability at 90 days (OR 2·07 [95% CI 1·47–2·93]) but there were no significant differences in symptomatic intracerebral haemorrhage. There were no significant differences in serious adverse events or mortality between groups. Interpretation: Intensive control of systolic blood pressure to lower than 120 mm Hg should be avoided to prevent compromising the functional recovery of patients who have received endovascular thrombectomy for acute ischaemic stroke due to intracranial large-vessel occlusion. Funding: The Shanghai Hospital Development Center; National Health and Medical Research Council of Australia; Medical Research Futures Fund of Australia; China Stroke Prevention; Shanghai Changhai Hospital, Science and Technology Commission of Shanghai Municipality; Takeda China; Hasten Biopharmaceutic; Genesis Medtech; Penumbra.